THE ACCOUNTANT’S PERSPECTIVE ABOUT THE REGULATION OF LAW 6380/19 - Domínguez Escobar, Andrea; Alegre Ramírez, Gabriela; Soledad Gómez, Sandra (Revista Gênero e Interdisciplinaridade, 2023)
This research work aims to demonstrate the knowledge that professionals have about the new tax regulations, since it is important because it helps to have a better control of the declarations of each tax. Our quantitative approach gave us statistical data with more accurate results, a descriptive investigation was planned, through closed surveys to know exactly what the real situation is, resulting in professionals handling the new regulation of law 6380/19. It is important to highlight that professionals do not agree with the new implementation of the law that unifies taxes, on the other hand, they are dissatisfied with the training provided by SET.